KONFLIK BATIN TOKOH UTAMA NOVEL TEMBANG ILALANG KARYA MD. AMINUDDIN TAHUN PELAJARAN 2012/2013 - Wahlin, Wahlin; Nasution, Ismail; Helda, Trisna (Pendidikan Bahasa Indonesia, 2013)
The research was distributed by inner conflict and about the labyrinth of the life of a character named Asroel who was often confronted with environments that are less supportive of his efforts. Formulation of the problem of the research is "How does the main character in the novel the inner conflicts of traditional Thatch work MD. Aminuddin reviewed aspects of the id, ego and super ego "? The purpose of this study is to describe and explain the inner conflict protagonist of the novel the song of reeds by MD. Aminuddin reviewed aspects of the id, ego and super ego by using the theory of Sigmund Freud propounded.This type of research is qualitative research using descriptive method. The Data in this study are the elements (of text) that supports the inner conflict in the novel Song of reeds By MD. Aminuddin. The data source is a novel Song of reeds by MD. Aminuddin. This research is carried out by stages: (1) read and understand novel Song of reeds by MD. Aminuddin, (2) identify and classify data inner conflict in the novels main character, (3) determining the inner conflict of the main character aspects of the id, ego and super ego, interpret the data (4), (5) prove and formulate conclusions.The analysis of research data shows that the main character (Asroel) experiencing inner conflict; (1) aspects of id make Asroel sad because his farewell with Roekmini and his son. Then Asroel Stienjie Netherlands girl loves totok, (2) the ego aspect makes the Asroel into a hard figure in maintaining the opinion that impact on himself. Asroel can not be balancing aspects of the id, ego and super ego makes it erred in taking decisions, (3) aspects of super ego finally made Asroel aware of his wrong doing that maintains his ego all along to make the Asroel stuck into a variety of difficult situations. Suggestions in this study is expected to be for the reader not concerned with ego, and balancing between id, ego and super ego.Â